PENGARUH INVESTMENT OPPORTUNITY SET, AUDIT TENURE DAN REPUTASI KAP TERHADAP AUDIT REPORT LAG (EMITEN BASIC MATERIALS BURSA EFEK INDONESIA PERIODE 2021-2023) - Putri, Syafina Amira; Mukti, Aloysius Harry; Eprianto, Idel (SINERGI : Jurnal Riset Ilmiah, 2025)
The research aims to examine the Investment Opportunity Set, Audit Tenure and KAP Reputation on Audit Report Lag. The research population is all issuers in the Basic Materials Sector of the Indonesian Stock Exchange for the period 2021-2023. The research variable Audit Report Lag is the dependent variable and Investment Opportunity Set, Audit Tenure and KAP Reputation are the independent variables. The sampling technique used a purposive sampling method and a sample of 192 issuers was obtained. Descriptive Statistical Analysis Methods, Classical Assumption Tests, Correlation Tests, Multiple Linear Regression Tests, and Hypothesis Testing. The research results show that Investment Opportunity Set, Audit Tenure and KAP Reputation have a negative effect on Audit Report Lag.